64.7k views
5 votes
If f(x) = 2x - 1 and g(x) = x^2 - 2, find [g · f](x)

please show me how to do this

User Dereleased
by
6.4k points

2 Answers

5 votes

Answer:

(x² -7)/(2x + 1)

Explanation:

f(x) = 2x+1 and g(x) = x² -7

thus: (g/f)(x) = g(x)/f(x) = x² -7/2x + 1

User Sujay Sreedhar
by
6.1k points
7 votes

Hello!

The answer is:


(g \circ f)(x)=4x^(2)-4x-1

Why?

To solve the problem, we need to remember that composing functions means evaluate a function into another different function.

Also, we need to remember how to solve the following notable product:


(a-b)^(2)=a^(2)-2ab+b^(2)

We have that:


(g \circ f)(x)=g(f(x))

Now, we are given the equations:


f(x)=2x-1\\g(x)=x^(2)-2

So, composing we have:


(g \circ f)(x)=g(f(x))


(g \circ f)(x)=(2x-1)^(2)-2

Now, we have to solve the notable product:


(g \circ f)(x)=((2x)^(2)-2(2x*1)+1^(2))-2


(g \circ f)(x)=4x^(2)-4x+1-2

Hence, we have that:


(g \circ f)(x)=4x^(2)-4x-1

Have a nice day!

User Blareprefix
by
6.2k points